SOCIO-PSYCHOLOGICAL FACTORS INFLUENCING THE DYNAMICS OF PSYCHOLOGICAL WELL-BEING AMONG MARRIED STUDENTS (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article examines the socio-psychological factors influencing the dynamics of psychological well-being among married students. The study considers psychological well-being as a multidimensional condition connected with emotional stability, life satisfaction, self-acceptance, interpersonal relations, academic adaptation and the ability to balance family and educational responsibilities. Married students often experience a specific combination of social roles, since they are required to perform simultaneously as learners, spouses, parents in some cases and active members of the social environment. These overlapping roles may create both supportive and stressful conditions for personal development. The article analyzes the influence of family support, marital relationships, academic workload, financial pressure, social expectations, gender-role attitudes, communication patterns and institutional support on the psychological state of married students. Special attention is given to the dynamic nature of well-being, which may change depending on adaptation to marriage, educational demands, interpersonal conflicts and personal coping strategies. The study emphasizes that psychological well-being among married students should be understood not only as the absence of stress or anxiety but also as the presence of resilience, emotional regulation, social support and meaningful life orientation. The article substantiates the need for psychological counseling, family-oriented educational support and preventive measures in pedagogical universities.